Analysis of flavour compounds and prediction of sensory properties in sea buckthorn (Hippophae rhamnoides L.) berries - Ma XY; Yang W; Marsol-Vall A; Laaksonen O; Yang BR (WILEY, 2022)
The aim of this study was to investigate sugars, organic acids, flavonol glycosides (FGs), proanthocyanidins and volatiles as flavour compounds in sea buckthorn (SB) berries of five cultivars and to predict the sensory properties of berries. The profiles of flavour compounds in SB berries varied significantly among the cultivars. Total proanthocyanidins and FGs were highest in 'Pertsik' and 'Raisa', respectively. Total volatiles were highest in 'Vorobyevskaya' and lowest in 'Raisa'. A previously established PLS model was used to predict the sensory properties of SB berries based on the non-volatile flavour compounds. The mouth-drying astringency can be predicted the most reliably, which has the highest regression coefficients with quinic acid, isorhamnetin-3-O-sophoroside-7-O-rhamnoside and total proanthocyanidins. Bitterness cannot be predicted using the model. 'Pertsik' berries were predicted to be more mouth-drying astringency and sour than those of 'Raisa'. The research supports the cultivar selection in cultivation and industry of SB berries.